The Importance of Trichoscopy in Clinical Practice - Ana Filipa Pedrosa; Paulo Morais; Carmen Lisboa; Filomena Azevedo (Dermatology Research and Practice)
Trichoscopy corresponds to scalp and hair dermoscopy and has been increasingly used as an aid in the diagnosis, follow-up, and prognosis of hair disorders. Herein, we report selected cases harbouring scalp or hair diseases, in whom trichoscopy proved to be a valuable tool in their management. A review of the recent literature on this hot topic was performed comparing the described patterns with our findings in clinically common conditions, as well as in rare hair shaft abnormalities, where trichoscopy may display pathognomonic features. In our view, trichoscopy represents a valuable link between clinical and histological diagnosis. We detailed some trichoscopic patterns, complemented with our original photographs and our insights into nondescribed patterns.